The plant cultivation situation of Transcarpathia in the Khrushchev era (1953–1964) - Вароді Наталія; Váradi Natália; Natalia Varadi (Видавничий дім «Гельветика», 2021)
Abstract. After Stalin’s death, N. Khrushchev emerged victorious from the political struggle. Then, after the execution of L. Beria, head of the Soviet secret service, communist dictatorship was replaced by a period of total oligarchy. The period between 1953 and 1964 can be seen as the era of “thaw”. N. Khrushchev implemented a number of reforms, but the reform era turned into recentralization, causing Khrushchev’s failure. Due to its geopolitical situation, Transcarpathia received significant attention from Soviet leaders. The area was of strategic importance in terms of transport from east to west, it was considered a «western gate». The Chop – Batevo area became one of the most important transhipment stations in the Soviet Union. Transcarpathia had been economically integrated into the Soviet system since 1946 and became part of the Ukrainian SSR economy. Planbased management was implemented in all areas of agriculture. Despite the fact that a lot of work was devoted to the political and economic history of Transcarpathia during the «thaw», the peculiarities of the reform of agriculture in the region at this time were not in the center of attention of scientists. The aim of this article is to find out the key features of the plant cultivation situation of Transcarpathia in the Khrushchev era (1953–1964). The key areas of crop production in Transcarpathia during the time of N. Khrushchev were domestication of tea and citrus plants, the great Party cereal (corn) program, and growing of vegetables, fruits and grapes. The plan for the domestication of tea and citrus plants failed because the kolkhozes were unable to meet the plans regarding the tea plantations, mostly due to frost damage to the plants. A number of problems arose in corn production as well. Orcharding and viticulture were relatively successful even in the mountain areas. Plan-based Soviet management was unable to satisfy all needs of Transcarpathian crop production during the time of N. Khrushchev.

Резюме. Після смерті Сталіна переможцем політичної боротьби вийшов М. Хрущов. Потім, після страти Л. Берії, голови радянської спецслужби, комуністична диктатура змінилася періодом тотальної олігархії. Період між 1953 і 1964 рр. можна розглядати як епоху «відлиги». М. Хрущов здійснив низку реформ, але період реформ переріс у рецентралізацію, що спричинило провал М. Хрущова. Завдяки своєму геополітичному становищу Закарпаття привертало увагу радянського керівництва. Район мав стратегічне значення з погляду транспортного сполучення між Сходом і Заходом, його вважали «західними воротами». Район «Чоп – Батєво» став однією з найважливіших перевантажувальних станцій Радянського Союзу. Із 1946 р. Закарпаття було економічно інтегроване до радянської системи та стало частиною народного господарства Української РСР. У всіх галузях сільського господарства впроваджувалося планове управління. Незважаючи на те, що політичній та економічній історії Закарпаття в період «відлиги» присвячено багато праць, особливості реформування сільського господарства краю в цей час не потрапляли в центр уваги науковців. Мета статті – з’ясувати основні особливості в становищі рослинництва Закарпаття хрущовської доби (1953–1964). Основними напрямами рослинництва Закарпаття за часів М. Хрущова були доместикація чаю та цитрусових, велика партійна злакова (кукурудзяна) програма, вирощування овочів, фруктів і винограду. План доместикації чаю та цитрусових провалився, оскільки колгоспи не змогли виконати плани щодо чайних плантацій, здебільшого через пошкодження рослин унаслідок морозів. Низка проблем виникла й у виробництві кукурудзи. Садівництво та виноградарство були порівняно успішними навіть у гірських районах. Планове радянське керівництво було не в змозі задовольнити всі потреби закарпатського рослинництва за часів М. Хрущова.
Ситуація в рослинництві Закарпаття в епоху Хрущова (1953–1964)
Keywords: Transcarpathia 1953–1964; agriculture; plant cultivation; kolkhoz; sovkhoz; reform